Effects of Aloe vera extract on growth indices, carcass composition and bacterial flora in the intestine of Siberian sturgeon (Acipenser baerii) - Bazari Moghaddam, S.; Haghighi, M.; Sharif Rohani, M.; Hamidi, M.; Ghasemi, M. (2016)
Regarding the beneficial effects and benefits of the herb Aloe vera and its application in various industries such as pharmaceuticals and food industries, this study investigated the effects of Aloe vera extract on growth parameters and bacterial flora of the Siberian sturgeon (Acipenser baerii). In this study, a total of 360 numbers of Siberian sturgeon weighted average 10.95±0.04 (g) randomly distributed in four treatments including a control group and three experimental groups (each with three replications) were used. So, Aloe Vera extract powder ratio of 0.5%, 1% and 1.5% were added to the food. After eight weeks of feeding in the fiberglass vans and physicochemical parameters of water daily registration, biometry carried out and necessary samples collected. In this study, growth indicators such as weight gain, initial body weight, condition factor, feed conversion ratio, specific growth rate, protein efficiency ratio, hepatosomatic index and survival rate were calculated. Results showed that all growth parameters (except hepatosomatic index) in the treatments compared to the control group showed statistically significant differences as a significant difference between the control group treated 1.5% extract were observed (p<0.05). Each carcass composition parameters, no significant difference was observed between the treatment and control groups (p>0.05). Meanwhile, total count of bacteria in intestine in the treatment and control groups did not show significant differences (p>0.05), but significant increase in the count of anaerobic bacteria (lactic acid bacteria) were observed compared to the control group (p<0.05). The result showed that Aloe vera extract can be effective in improving the growth performance of Siberian sturgeon.